Uji Validitas dan Uji Reliabilitas Terhadap Faktor-Faktor yang Mempengaruhi Wisatawan Terhadap Pemilihan Wisata Halal - Meilina, Popy; Adharani, Yana; Dores, Ardiansyah (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2018)
Finding a right strategy to attract tourists is important for tourism businesses. Seeing that the majority of Indonesian population is Muslim, making tourism businesses hold a halal tour. However, it is also necessary to know the factors of tourists choosing a tourist destination so that tourism actors can make travel plans that make tourists choose them. So as to support this research, a questionnaire has been distributed to 50 potential tourists whose contents consist of respondent profiles, market conditions, marketing mix which consists of: products offered, prices, travel locations, promotions carried out, employees, programs offered, and cooperation. Questionnaires were processed with SPSS, based on the validity and reliability tests showed that respondents gave positive results for 27 variabels with Cronbach’s Alpha about 0.841 and KMO 0.725.